Phonic identity designing a sound-integrated cultural park to promote the heritage of the Las Pinas Bamboo Organ - Aquino, Johanna Venice R. (College of Architecture, University of the Philippines Diliman, 2019)
An important aspect of maintaining one's culture is heritage conservation. However, heritage conservation is limited as it mostly focuses on the visual aspect and rarely takes into consideration sound. A way of valuing sound in the landscape is through the application of soundscape ecology in heritage conservation. Soundscape ecology is an approach which utlizes sound as a resources and takes into consideration environmental noise reduction. One such culture that the Philippines has centered on sound is the Las Pinas Bamboo Organ. The organ is a natural cultural treasure and is an important part of Las Pinas culture. Yet people fail to see its full cultural importance. In order to conserve and promote the cultural sounds and the heritage of the organ, this thesis aims to integrate the culturally significant sounds of the organ as well as promote the organ's heritage through a cultural park.